Improving Student Learning Outcomes Through Discussion Strategies in Islamic Learning at SMP Negeri 2 Idanogawo - Siddiq, Ahmad Sangkot; Simatupang, Denar Yosafad; Zalukhu, Agus Fajarman (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to improve student learning outcomes in Islamic Education by using Discussion Strategy. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data of this study were obtained by test and observation techniques. Tests are used to improve student learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Learning with Discussion Strategy can improve student learning outcomes. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 46.56%, the first cycle 78.57% and in the second cycle increased to 89.77%. Thus, the use of Discussion Strategy can be used as an alternative to improve student learning outcomes.